2010
DOI: 10.1037/a0019466
|View full text |Cite
|
Sign up to set email alerts
|

Positive mood effects on delay discounting.

Abstract: Delay discounting is the process by which the value of an expected reward decreases as the delay to obtaining that reward increases. Individuals with higher discounting rates tend to prefer smaller immediate rewards over larger delayed rewards. Previous research has indicated that personality can influence an individual's discounting rates, with higher levels of Extraversion predicting a preference for immediate gratification. The current study examined how this relationship would be influenced by situational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
75
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 33 publications
(39 reference statements)
9
75
0
1
Order By: Relevance
“…This notion is consistent with work suggesting that affect and emotion play an important role in intertemporal choice (DeSteno, 2009;Hirsh, Guindon, Morisano, & Peterson, 2010;Loewenstein, 1996), and in (mis)predicting the preferences and emotions of others (Van Boven & Loewenstein, 2003). However, it may also be that when honesty is perceived to result in future benefits for a target that far outweigh the benefits of lying, compassion could lead individuals to be more honest.…”
Section: Discussionsupporting
confidence: 85%
“…This notion is consistent with work suggesting that affect and emotion play an important role in intertemporal choice (DeSteno, 2009;Hirsh, Guindon, Morisano, & Peterson, 2010;Loewenstein, 1996), and in (mis)predicting the preferences and emotions of others (Van Boven & Loewenstein, 2003). However, it may also be that when honesty is perceived to result in future benefits for a target that far outweigh the benefits of lying, compassion could lead individuals to be more honest.…”
Section: Discussionsupporting
confidence: 85%
“…One may therefore expect that in the context of altruistic punishment, positive emotions play an important role in initiating actions to restore violated fairness norms. Alternatively, it could be that positive affect fosters deviations from economical rational choices, as suggested by the research of Hirsh, Guindon, Morisano, and Peterson (2010), who showed a positive association between positive affectivity and impulsive responses, specifically with impulsive, reward-driven behavior in extraverts. In sum, these findings substantiate the importance of impulsive, emotional processes besides cognitive processes of social norm enforcement in altruistic punishment.…”
Section: Discussionmentioning
confidence: 99%
“…The tendency towards impulsive choice varies between individuals (e.g., Kirby & Marakovic, 1996;Shamosh & Gray, 2008). It is stronger in certain personality types (e.g., Hirsh, et al, 2010) and is associated with certain psychopathologies (e.g., Bobova, et al, 2009). Patients with attention deficit/hyperactivity disorder (ADHD) are more impulsive in this sense (Barkley et al, 2001), as are patients with schizophrenia (Heerey, et al, 2007); cocaine-addicts (Kirby & Petry, 2004), pathological gamblers (Dixon, et al, 2003), smokers (Businelle, et al, 2010) and alcoholics (Mitchell, et al, 2005;Petry, 2001); while the opposite seems to be the case for individuals with higher levels of intelligence (Shamosh & Gray, 2008).…”
Section: Introductionmentioning
confidence: 99%